Ein weiterer Bericht zur Anthribidenfauna Papua Neuguineas (Coleoptera: Anthribidae). - Frieser, Robert (Contributions to Entomology = Beiträge zur Entomologie, 1989)
In the following 15 species and 6 subspecies were described as new, also synonymical notes are given for some species, described by M’Leay from the Fly River. For the genera of Mucronianus Jordan, Rhaphitropis Reitter and Exillis Pascoe of the New Guinea species keys are added. Nomenclatural Acts eurous (Jordan, 1895) (Acorynus), comb. n. hitherto Hucus eurous angustefasciatus Frieser, 1989 (Acorynus cruralis), sspec. n. distans Frieser, 1989 (Exillis), spec. n. fasciger Frieser, 1989 (Exillis), spec. n. papuensis Frieser, 1989 (Exillis), spec. n. rectangulus Frieser, 1989 (Exillis), spec. n. sexcarinatus Frieser, 1989 (Exillis), spec. n. subparallelus Frieser, 1989 (Exillis), spec. n. woodlarkianus Frieser, 1989 (Exillis), spec. n. discoidales Frieser, 1989 (Exillis impressus), sspec. n. subcarinatus Frieser, 1989 (Exillis papuensis), sspec. n. instructa Frieser, 1989 (Genethila), spec. n. parvulus (M'Leay, 1856) (Hucus), comb. n. hitherto Litocerus parvulus cavicollis Frieser, 1989 (Mucronianus), spec. n. latifrons Frieser, 1989 (Mucronianus), spec. n. procerus Frieser, 1989 (Mucronianus), spec. n. subconvexus (M'Leay, 1856) (Mucronianus), comb. n. hitherto Litocerus subconvexus xenoceroides Frieser, 1989 (Mucronianus), spec. n. basiplaga Frieser, 1989 (Rhaphitropis), spec. n. continuus Frieser, 1989 (Rhaphitropis), spec. n. frater Frieser, 1989 (Rhaphitropis), spec. n. tricolor Frieser, 1989 (Rhaphitropis), spec. n. mancus Frieser, 1989 (Rhaphitropis basiplaga), sspec. n. papuensis Frieser, 1989 (Rhaphitropis limbalis), sspec. n. gazellae Frieser, 1989 (Rhaphitropis stephanus), sspec. n.